PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI LINGKUNGAN KALATIN KELURAHAN LOWU UTARA - Marland Novel Ponowu; Caroline Betsi Diana Pakasi; Audrey Julia Maria Maweikere (AGRI-SOSIOEKONOMI, 2019)
This study aims to support community empowerment and increase the income of the community in road infrastructure development in the Kalatin Village, North Lowu Subdistrict, Ratahan District. Data collection is carried out for 3 months, from June 2018 to August 2018. The collected data isarranged quantitatively collected in the form of a table with sample of 30 respondents. This study uses primary data and secondary data. Primary data were obtained from interviews and questionnaires for the people living in the Kalatin Village and secondary data obtained from the relevant agencies. The results of the study show how community empowerment through cooperation to carry out the construction of road infrastructure in the Kalatin Village is well run by the Kalatin Village community to do various forms of participation in the form of work and food and beverages. The construction of road infrastructure in the Kalatin Village provides an increase in revenue of 14.29% - 650% or 6 times the revenue when the road has not been repaired. This is because the road infrastructure access to the marketing of commodities both inside and outside the Kalatin Village.*erprm*